Notes to Philosophy 167: Class 4 -- Kepler's Planetary System and the Rudolphine Tables -- Part 15. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: An Examination of the Evidence for Kepler's "Laws": The Precise Statement of Kepler's Generalizations -- The Evidence in 1630 for the Ellipse and Area "Laws" -- The Evidence in 1630 for the 3/2 Power "Law" -- Evidence that the "Laws" are Laws: Kepler's Approach -- Kepler's Approach to the Underlying Physics -- Illustrate Via the "Physics" for Keplerian Motion -- The Empirical Limitations of Kepler's Physics -- Kepler's Methodological Legacy: Some Final Remarks: Kepler's Conception of "Scientific" Astronomy -- Some Residual Problems Facing Kepler in 1630 -- Issues Raised on His Conception by These Problems.; Generally corresponds to the video segment: Class 4, Part 15.